The Collision Between the Classroom Voice(s) and the Voice of the Mainstream Culture on End-of-Life to Cultivate Students' Attitudes Toward Death in China - Meng, Ling; Yi, Li; Li, Tian (Frontiers in Psychology, 2022)
Using Bakhtin’s (1984) notion of polyphony, this study explored the discussion of the end-of-life issues in the Course on Life and Death Education in one Chinese university. Ethnographic methods were adopted to investigate the collision between the classroom voices and the voices of the mainstream culture on end-of-life in the process of developing students’ attitudes toward death. The findings revealed that 1) “to understand death” involved challenging the voice of “strangeness and fear of death”; 2) “honestly facing up to and accepting the feelings of the fear, pain, and helplessness” was the response to “be brave”; and 3) the goal “to die peacefully” resisted the notion of “extending life at any cost”. Through the collision between these voices, students developed their attitudes toward death in facing, understanding, accepting and choosing how to die. The analysis further revealed that to provide one only “answer” to death by the teacher is not sufficient or effective to foster students’ attitudes toward death because the students are a diverse group holding different views on the end-of-life issues, which demonstrated the importance of creating dialogues in the life and death education.